Professional competence required in advanced practice nursing in critical care: An exploratory qualitative study - Marianne Trygg Solberg; Ingunn Pedersen; Cathrine Mathisen; Inger Johanne Finnstrøm; Per Kristian Lundin; Andréa Aparecida Gonçalves Nes (Nursing Open, 2023)
Abstract Aim To identify the required competencies of advanced practice nurses (APNs) working with patients in critical care units in Norway. Design An exploratory qualitative design. Methods Four focus group interviews were performed with 18 nurses who worked in critical care units. The data were examined by inductive content analysis following Graneheim and Lundman's approach. Findings Our study found that APNs in critical care require the following professional competencies to meet the needs of patients characterised by greater age, comorbidities and increased complexity: (1) intrapersonal skills as revealed in the subthemes of self‐awareness; motivation and commitment; strong mental health and upholding ethical standards, (2) advanced clinical decision‐making skills as identified in the subthemes of integration of theory and practice; complex practical and technical skills; dealing with increased delegated responsibility and taking the lead in managing increased practice complexity and (3) interpersonal skills, including peer guidance, practising collaboratively and the ability to position oneself.